Pengaruh Banking Service Quality (BSQ) Terhadap Kepuasan Nasabah Dan Dampaknya Terhadap Loyalitas Nasabah Pada Bank CIMB Niaga Syariah Padang - Yulia Nerise Fitriensi; Dasep Suryanto; Adriansyah Adriansyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
This research will advance the Bahia and Nantel's research by studying the impact of Bahia and Natel's BSQ dimensions toward customer satisfaction and its influence on customer loyalty. This study being held in Bank CIMB Niaga Syariah, Padang Branch in West Sumatera Province. 190 respondents had been took as a samples in this study by using convenience sampling method. Primary data had been obtained through questionnaires. Data analysis method which used in this study is Structural Equation Modelling. The findings shows that BSQ's dimensions have a positive and significant impact toward customer satisfaction, moreover customer satisfaction have a positive and significant impact toward customer loyalty. Based on those results, so it been concluded that tangible must have an extra attention in order to increase the customer satisfaction.